Biblical Narrative and Palestine’s History: Changing Perspectives 2. By Thomas L. Thompson - Grabbe, Lester L. (The journal of theological studies, 2014)
T. L. Thompson, emeritus professor of Copenhagen University, has collected 19 essays that exemplify the development of his life’s work on the history of ancient Palestine. They are prefaced by a highly perceptive Introduction from Philip R. Davies, who shows how the different essays mark the progress and changing perspective of Thompson’s outlook on Palestinian history, and especially how the biblical text is to be related to this task of writing such a history. Thompson’s first important work—and the one making the greatest impact on biblical and historical scholarship—was his Historicity of the Patriarchal Narratives (1974). He also contributed to the seminal Israelite and Judean History (1977, edited by J. H. Hayes and J. M.